Marketing characteristics of Tokaj wine specialities based on factor and cluster analyses - Kárpáti, László; Szakál, Zoltán (Applied Studies in Agribusiness and Commerce, 2009)
The marketing kind of analysis in the domestic and international markets of Tokaj’s wine speciality has not happend yet. The present research scientific method supportedly defines the consumers of Tokaj’s wine speciality and it determinates the overlay receipt. The basis of the questionnaire research at the wine consumers cirlce is a representative sample of 1179 people. It confirms the truthfulness with factos and cluster dissection. On the hungarian market 5 sections can be devided, which has been determined by the earning category, the wine savvy and the referene price interval. Tokaj Wine Specialities named “late vintage” are also available. This name can be confusing for the consumer, some do not understand in what they differ from other Tokaj Wine Specialities, as actually all Tokaj Wine Specialities are late vintage wines; particularly, wine is harvested later than usual, occasionally in October or November. The findings obtained during the research can beutilised in practice, too. In accordance with the results and conclusions, we have several practical suggestions. Our methodological suggestion is that the result of the cluster analysis based upon a large number of representative sample should be cross-checked with focus group tests; what is more, upon justification and verification, a detailed analysis of the given segments can also be performed better with this method. It would be worth studying the exact reasons for the popularity of wines with the name ”late vintage”. Such types of Tokaj Wine Specialities should be given higher priority in marketing terms. My suggestion is that the type of wine accepted and liked by consumers should be kept count of as TokajWine Specialities officially, too. The future marketing strategy has to be developed by knowing the sections and by it’s further research which has to integrate to the strategy of Tokaj’s wine region.